2012
DOI: 10.1088/0022-3727/45/21/215304
|View full text |Cite
|
Sign up to set email alerts
|

Structural depth profile and nanoscale piezoelectric properties of randomly oriented Pb(Zr0.50Ti0.50)O3 thin films

Abstract: The structural properties of Pb(Zr0.50Ti0.50)O3 thin films with no preferential orientation were studied throughout the film thickness. An analysis on depth profile shows the existence of a significant (1 0 0) alignment near the film–electrode interface. Nanoscale piezoelectric measurements demonstrate the existence of a self-polarization effect in the studied films. An increase in this effect with film thickness increasing from 200 to 710 nm suggests that Schottky barriers and/or mechanical coupling near the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…This indicates that the alignment of domains occurs locally and these domains are oriented towards the bottom electrode. Such effect has already been discussed in the literature to a great extent [27][28][29][30][31][32][33]. Whatever be the origin of this self-polarization effect in BFCO film, one thing is clear in present case that it occurs on doping at Fe-site and disappears with co-doping at Bi-site.…”
Section: Introductionsupporting
confidence: 52%
“…This indicates that the alignment of domains occurs locally and these domains are oriented towards the bottom electrode. Such effect has already been discussed in the literature to a great extent [27][28][29][30][31][32][33]. Whatever be the origin of this self-polarization effect in BFCO film, one thing is clear in present case that it occurs on doping at Fe-site and disappears with co-doping at Bi-site.…”
Section: Introductionsupporting
confidence: 52%
“…7 At the films studied in the present work, |P i | increases with film thickness increasing suggesting that Schottky barriers cannot be a mechanism responsible for the selfpolarization effect for studied PZT films with no preferential orientation. 27 The fact that |P i | increases with increasing film thickness indicates that our films are polarized by an internal bias electric field strongly dependent of the film thickness, within the thickness range studied. Thus, we can exclude the effect of space charges located at the film-substrate interface and mechanical coupling between film-substrate as main mechanisms responsible for the self-polarization effect in the studied PZT films.…”
Section: Resultsmentioning
confidence: 82%
“…In this figure, P i presents essentially the same value for films with thicknesses between 200 nm and 380 nm but increases almost linearly for negative values from 500 nm up to 710 nm in thickness. The P i / d 33 =e 0 relation provides a qualitative description for the self-polarization effect in our PZT films, 27 where d 33 is the maximum piezoresponse distribution before poling in Figure 9(a) and e 0 is the real part of the dielectric permittivity of the respective film in Figure 6(a). This relation is reasonable if we consider that the coupling between the longitudinal piezoelectric coefficient (d 33 ) and the dielectric permittivity (e 0 ) and polarization (P) can be described by the equation d 33 ¼ 2Q 11 e 0 e 0 P, where Q 11 is the electrostriction coefficient and e 0 is the dielectric permittivity of vacuum.…”
Section: Resultsmentioning
confidence: 99%
“…For these films, it was observed that total polarization decreases as the film thickness increases, indicating that the films are polarized by an internal bias field near the bottom film-substrate interface [7]. The behavior is quite different for our films, which suggests that Schottky barriers and mechanical coupling near the film-substrate interface are not the main mechanisms responsible for the selfpolarization effect in the studied films with no preferential orientation [6]. The fact that |P i | increases with increasing film thickness indicates that our films are polarized by an internal bias electric field strongly dependent of the film thickness, within the thickness range studied.…”
Section: Figures 2(a) and 2(b) Shows Microstrain ('D/d) Andmentioning
confidence: 76%
“…As the studied PZT films in the present work present essentially the same grain size for different thickness, the extrinsic contributions are probably the main factors responsible for the behavior shown in Figure 4(a). [6]. These results were compared with the data taken after poling the same area with positive and negative voltages in Figure 5(b), where both poled and unpoled regions of the film were imaged simultaneously.…”
Section: Figures 2(a) and 2(b) Shows Microstrain ('D/d) Andmentioning
confidence: 99%